2023
DOI: 10.1038/s42003-023-04748-8
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase-like 2 processing by factor Xa modulates its activity and substrate preference

Abstract: Lysyl oxidase-like 2 (LOXL2) has been identified as an essential mediator of extracellular matrix (ECM) remodeling in several disease processes including cardiovascular disease. Thus, there is growing interest in understanding the mechanisms by which LOXL2 is regulated in cells and tissue. While LOXL2 occurs both in full length and processed forms in cells and tissue, the precise identity of the proteases that process LOXL2 and the consequences of processing on LOXL2’s function remain incompletely understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Thus, females appear to have a compensatory increase in prototypic LOX activation following induction of experimental hypertension, but not males. Previous studies have shown that LOXL2 processing shifts its substrate preference from Collagen IV to Collagen I in VSMCs 24 and the prototypic active LOX also exhibits preference for Collagen I. Consistent with the increase in active LOX and processed LOXL2, a significant increase in Collagen I abundance and a decrease in Collagen IV abundance was noted in the aortic ECM with Ang II infusion.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Thus, females appear to have a compensatory increase in prototypic LOX activation following induction of experimental hypertension, but not males. Previous studies have shown that LOXL2 processing shifts its substrate preference from Collagen IV to Collagen I in VSMCs 24 and the prototypic active LOX also exhibits preference for Collagen I. Consistent with the increase in active LOX and processed LOXL2, a significant increase in Collagen I abundance and a decrease in Collagen IV abundance was noted in the aortic ECM with Ang II infusion.…”
Section: Discussionsupporting
confidence: 71%
“…A qualitative increase in collagen content was noted with Ang II infusion by Masson’s trichrome and MOVAT pentachrome staining in both WT and Loxl2 +/- male mice and WT female mice (Figure 5Ai, Aii). However, the stains do not allow us to distinguish the specific subtypes of collagen, particularly Collagen I and IV, that are known substrates of LOXL2 24 . We therefore next evaluated LOX, LOXL2, Collagen I, and Collagen IV protein abundance in the aortic ECM by Western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primarily, LOX enzymes promote the first step in the formation of covalent cross-linking to stabilize collagen fibrils [ 12 , 50 , 51 ]. Specifically, for fibrillar type I collagen, it has been reported that LOX and LOXL2 can form covalent cross-links in the molecule [ 52 ]. It has also been demonstrated that LOX, LOXL2 and LOXL4 cross-link collagen IV, along with indications that LOXL4 cross-links IV via an increase in collagen IV deposition in vascular matrix remodeling [ 47 , 53 , 54 , 55 ].…”
Section: Enzymatic Collagen Cross-linking Mediated By Lysyl Oxidasesmentioning
confidence: 99%
“…Factor Xa cleaves LOXL2 at the beginning of SRCR3 (site R338↓). LOXL2 processing by factor Xa results in reduced cross-linking activity in the ECM and a change in LOXL2 substrate preference from collagen type IV to type I collagen [ 93 ].…”
Section: Control Of Loxl2 Expressionmentioning
confidence: 99%